Identification of the application features of finishing processing methods of parts with free abrasives at railway rolling stock repair enterprises - Romanchenko, Oleksiy; Tkachenko, Viktor; Shumakova, Tetiana (Technology audit and production reserves, 2025)
The object of research is the technological process of vibration finishing of the “Rotor Sheet” type flat parts, which are made of thin sheet metal at the enterprises of the railway industry of Ukraine in the process of repairing electric motors of rolling stock. Due to the peculiarities of operation, such parts often have residual defects after laser cutting – burrs, sharp edges, contamination – which negatively affect their further functioning. One of the most problematic areas is ensuring uniform, high-quality processing of a large number of thin parts simultaneously without their deformations and damages. During the study, methods of comparative analysis of technological solutions, experimental testing of vibration processing parameters and selection of the most effective operating modes of the machine were used. A selection of abrasive tools of various shapes and compositions was made and the influence of active alkaline solutions was studied, as well as the design of three structurally different special devices for placing parts in a container. The presented devices ensure positioning of the part with simultaneous access of the abrasive tool to all surfaces being processed. The research results can be used to design processing technologies for various types of flat parts made of thin sheet metal. A rational technological process has been obtained that allows for effective removal of surface defects, improving the quality of processing while maintaining high productivity. This is due to the fact that the proposed approach combines precise selection of processing modes and improved devices, in particular by controlling the movement of parts and optimal distribution of the working environment. This provides the possibility of obtaining high surface quality indicators with a significant reduction in processing time. Compared with similar known methods, this provides improved technological controllability, cost-effectiveness and adaptability to the conditions of mass production in mechanical engineering.